Optimizing the Preservation of Fresh Tomatoes into Tomato Dates to Increase the Shelf Life of Vegetable Food - Mansur, Ahmad; Ardi, Rudi Prasetyo; Mistriani, Nina (Budapest International Research and Critics University, 2021)
Tomato is currently one of the high economic value horticultural commodities and still requires serious treatment, especially in terms of increasing the yield and growth of tomatoes. This research will be carried out by Hospitality Laboratory in STIEPARI Semarang. The material used is tomato and sugar. The method used is making tomato dates, observing the deterioration kinetics of tomato candied quality, estimating shelf life of tomato sweets and adding sugar. The results of this study indicate that preservation of fresh tomatoes into tomato dates to increase the storability of plant foods (P <0.05). Vegetable food has a high fiber content so that the physical properties of plant foods, so that with a preservation system using sugar can increase the shelf life of vegetable products. Research result Based on the organoleptic results (color) of tomato dates presented in the table, it shows that tomato dates with the addition of sugar as much as T0 (0% Tomato Dates 0% Sugar), T1 (Tomato Dates 30% Sucrose) both were still in the like category, while T2 Tomato Dates were 30% Lactose) and T3 Tomato Dates 30% Fructose) both were in the very like category. Based on the organoleptic results (aroma) of tomato dates presented in the table, it shows that tomato dates with the addition of sugar as much as T0 (0% Tomato Dates 0% Sugar), T1 (Tomato Dates 30% Sucrose) and T2 (Tomato Dates 30% Lactose) are still in the category likes, while T3 Tomato Dates 30% Fructose) is in the very like category. While at T2 (30% Lactose Tomato Dates) showed liking, and T3 Tomato Dates 30% Fructose) showed very liking. While the formula T3 Tomato Dates 30% Fructose) which shows the category of very like. namely the addition of 40gr lactose as much as 84% while the lowest lactose content was the addition of 20gr lactose as much as 20gr.